As ideias de defesa social no sistema penal brasileiro: entre o garantismo e a repressão (de 1890 a 1940) - Santos, Bartira Macedo de Miranda (2010)
This research seeks to demonstrate the significance of social protection ideas that have shaped the criminal justice system like the Criminal Code and the 1940 s Code of Criminal Procedure. It discusses the ideas of social defense made by the Italian Positive School, as justification of the punitive system. For this school, the social defense is the reason of criminal justice. Given the biological determinism of the born criminal, Lombroso, Ferri and Garofalo are committed to building a criminal science that is able to promote an effective social defense. Appart from the metaphysical approach of the classics and its theorizing abstract regarding the legal concept of crime, the Italian positivists sought to understand the causes of crime within the criminal person, replacing the deductive method by the inductive one. From 1884 the anthropological positivism was widely spread in Brazil. By not having their proposals adopted by the Criminal Code of 1890, the positivists have used this law, the fame of "the worst of all the known codes . Originally from the legal discourse, the social defense shall be incurred, since the first decades of the twentieth century, as a movement of Criminal Policy with a strong influence on the laws of the period, including the Brazilian laws